FEATURES OF THE USE OF ICT IN SPEECH THERAPY PRACTICE OF PRESCHOOL INSTITUTIONS - Khilya, Anna; Korol, Alona Valeriiva (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Today, an important part of work in a preschool institution is working with children with disabilities in the development of speech. Since the formation of speech skills in children at this age has a number of features and requires attention for further socialization and self-realization of the child.That is why in the article we analyze the state of modern psychological and pedagogical research on the feasibility and prospects of using information and communication technologies in the practice of speech therapist, in particular, in preschool educational institutions. As part of a study conducted based on the work of speech therapists in a preschool institution and a private educational organization – a speech club, we established that information and communication technologies are able to provide computerisation and high efficiency of the process of the development and speech correction of children with speech impairments. Obstacles to the introduction of such technologies into the practice of speech therapy are identified and ways to overcome obstacles and difficulties in solving the problems of computerisation of the speech therapy process are presented.We have proved the increase of effectiveness of the speech therapy process as a result of remote interaction of a speech therapist with teachers, parents and the public using ICT.